Modelling and Optimization of Orientated Beam with Tip Mass for Vibration Energy Harvesting using Piezoelectric Patches - Wali, Laxmi. B.; Chandrasekhara, C V (Journal of Mines, Metals and Fuels, 2023)
Energy harvesting is extracting energy from ambient sources. Vibration energy harvesting area have received attention of many researchers to power wireless sensors and low-power electronic devices from smart materials. In literature, authors have focused on analytical and finite element models of cantilever beam with tip mass. The paper focuses on the novel numerical technique for orientated cantilever beam bounded with piezoelectric patches and mounted with tip mass using the direct method with non-orthonormalisation to derive the frequency response function (FRF) for voltage, current and power output. MatLab programme is developed considering the Euler Bernoulli beam assumptions, constitutive equations of piezoelectric material and Hamilton’s principle. The MatLab programme is validated with the previous work on orthonormalisation electro-mechanical finite element for unimorph beam and good agreement is obtained. The dynamic characteristics of considered model is presented and optimized parameters are obtained.